Pocketbook based on local wisdom and its effectivity in improving students' knowledge on the utilization of traditional medicine plants - Alif Yanuar Zukmadini; K Kasrina; Dewi Jumiarni; Syaiful Rochman (Biosfer: Jurnal Pendidikan Biologi, 2020)
Nowadays, young generation's knowledge about local wisdom in utilizing medicinal plants is decreasing. This study aimed to develop a pocketbook of antimicrobial medicinal plants based on local wisdom of the Serawai and Muko-Muko tribes (PAMP-LWSMT) in Bengkulu Province-Indonesia and its effectiveness in improving students' knowledge about the utilization of plants as traditional medicine (UPTM). This type of research was a research and development (R&D) of Sugiyono, it had 10 stages. Five stages have been conducted and published in 2018 and will be continued to the last five stages, namely product trials, product revision, trial use, product revision, and mass production. The results showed that 1) pocketbooks had a good response for students and teachers. It can be identified from averaged score of teacher response (75,33) and average score of children's response (65,31) 2). Pocketbook was quite effective to increase students’ knowledge about the utilization of plants as traditional medicine. It can be shown from N-gain value (0.5413). Value of Sig. (2-tailed) was 0,000 it means there was a significant difference before and after using a pocketbook. Through the development and effectiveness of pocketbooks, it can preserve the values of the local wisdom of the Serawai and Muko-Muko tribes in utilizing plants as medicine. This pocketbook is recommended to be used widely as a learning resource for high school students in various districts in Bengkulu Province so that students' knowledge can develop.